Genome-wide scan identifies CDH13 as a novel susceptibility locus contributing to blood pressure determination in two European populations. - Org, E; Eyheramendy, S; Juhanson, P; Gieger, C; Lichtner, P; Klopp, N; Veldre, G; Döring, A; Viigimaa, M; Sõber, S; Tomberg, K; Eckstein, G; et al. (2009)
Hypertension is a complex disease that affects a large proportion of adult population. Although approximately half of the inter-individual variance in blood pressure (BP) level is heritable, identification of genes responsible for its regulation has remained challenging. Genome-wide association study (GWAS) is a novel approach to search for genetic variants contributing to complex diseases. We conducted GWAS for three BP traits [systolic and diastolic blood pressure (SBP and DBP); hypertension (HYP)] in the Kooperative Gesundheitsforschung in der Region Augsburg (KORA) S3 cohort (n = 1644) recruited from general population in Southern Germany. GWAS with 395,912 single nucleotide polymorphisms (SNPs) identified an association between BP traits and a common variant rs11646213 (T/A) upstream of the CDH13 gene at 16q23.3. The initial associations with HYP and DBP were confirmed in two other European population-based cohorts: KORA S4 (Germans) and HYPEST (Estonians). The associations between rs11646213 and three BP traits were replicated in combined analyses (dominant model: DBP, P = 5.55 x 10(-5), effect -1.40 mmHg; SBP, P = 0.007, effect -1.56 mmHg; HYP, P = 5.30 x 10(-8), OR = 0.67). Carriers of the minor allele A had a decreased risk of hypertension. A non-significant trend for association was also detected with severe family based hypertension in the BRIGHT sample (British). The novel susceptibility locus, CDH13, encodes for an adhesion glycoprotein T-cadherin, a regulator of vascular wall remodeling and angiogenesis. Its function is compatible with the BP biology and may improve the understanding of the pathogenesis of hypertension.